A reluctant bride - Hedlund, Jody (Hedlund, Jody. Bride ships, 2019)
In 1862, Mercy escapes a bleak future in London and joins a bride ship. Wealthy and titled, Joseph becomes the ship's surgeon to avoid the pain of losing his family. He has no intention of settling down, but when Mercy becomes his assistant, they must fight against a forbidden love.